2017
DOI: 10.1016/j.celrep.2017.11.103
|View full text |Cite
|
Sign up to set email alerts
|

Serine-Dependent Sphingolipid Synthesis Is a Metabolic Liability of Aneuploid Cells

Abstract: SUMMARY Aneuploidy disrupts cellular homeostasis. However, the molecular mechanisms underlying the physiological responses and adaptation to aneuploidy are not well understood. Deciphering these mechanisms is important because aneuploidy is associated with diseases including intellectual disability and cancer. Although tumors and mammalian aneuploid cells including several cancer cell lines show altered levels of sphingolipids, the role of sphingolipids in aneuploidy remains unknown. Here we show that ceramide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 54 publications
(64 reference statements)
0
59
0
Order By: Relevance
“…More recently, highly aneuploid colorectal cells were found to be sensitive to an antagonist of ceramide glucosyltransferase due to overabundance of intracellular ceramide, possibly as a result of dysregulated sphingolipid metabolism (Tang et al, 2017). It was also shown that ceramide levels were increased in some aneuploid budding yeast strains and further increasing ceramide levels either genetically or pharmacologically could slow down their proliferation (Hwang et al, 2017). …”
Section: Aneuploidy-associated Stressmentioning
confidence: 99%
“…More recently, highly aneuploid colorectal cells were found to be sensitive to an antagonist of ceramide glucosyltransferase due to overabundance of intracellular ceramide, possibly as a result of dysregulated sphingolipid metabolism (Tang et al, 2017). It was also shown that ceramide levels were increased in some aneuploid budding yeast strains and further increasing ceramide levels either genetically or pharmacologically could slow down their proliferation (Hwang et al, 2017). …”
Section: Aneuploidy-associated Stressmentioning
confidence: 99%
“…In yeast, several aneuploidy-specific cellular vulnerabilities have been described [18][19][20] . For example, aneuploid budding yeast have elevated levels of proteotoxic stress, presumably due to the perturbation of the required stoichiometry of protein complexes 19 .…”
mentioning
confidence: 99%
“…For example, aneuploid budding yeast have elevated levels of proteotoxic stress, presumably due to the perturbation of the required stoichiometry of protein complexes 19 . Another example is the increased sensitivity of aneuploid yeast to perturbation of sphingolipid metabolism 20,21 . Although some of these findings were successfully recapitulated in mammalian cells 21,22 , the systematic identification of aneuploidy-induced vulnerabilities remains elusive in human cancer.…”
mentioning
confidence: 99%
“…GARP deficiency results in accumulation of sphingolipid synthesis intermediates [151]. Also from this cluster came fatty acid elongase activity ( FEN1/ELO2 and SUR4/ELO3 ), which when deficient leads to reduced ceramide production and phytosphingosine accumulation [152, 153].…”
Section: Resultsmentioning
confidence: 99%